Bringing inequality back in - Heather Boushey (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Economic inequality has traditionally not been the center of mainstream macroeconomic thought. Rethinking whether and how today's high economic inequality – along all axes, not just income – affects economic growth and stability is an increasingly relevant and important field of inquiry. This paper investigates how economic research can inform the debate on the relationship between inequality and growth. I define the relationship between inequality and growth as well as briefly review the literature on their relationship. Then, I outline the channels through which inequality may affect growth. And finally, I address possible avenues for public policy going forward.
Keywords: O40; I24; D63; D31; 330; inequality; economic growth; public policy